Novel reliable routing method for engineering of internet of vehicles based on graph theory. Issue 1 (13th December 2018) - Zhang, De-gan; Tang, Ya-meng; Cui, Yu-ya; Gao, Jing-xin; Liu, Xiao-huan; Zhang, Ting
Abstract : Purpose: The communication link in the engineering of Internet of Vehicle (IOV) is more frequent than the communication link in the Mobile ad hoc Network (MANET). Therefore, the highly dynamic network routing reliability problem is a research hotspot to be solved. Design/methodology/approach: The graph theory is used to model the MANET communication diagram on the highway and propose a new reliable routing method for internet of vehicles based on graph theory. Findings: The expanded graph theory can help capture the evolution characteristics of the network topology and predetermine the reliable route to promote quality of service (QoS) in the routing process. The program can find the most reliable route from source to the destination from the MANET graph theory. Originality/value: The good performance of the proposed method is verified and compared with the related algorithms of the literature.